STUDI PENGARUH AREA PERKERASAN TERHADAP PERUBAHAN SUHU UDARA (Studi Kasus Area Parkir Plaza Senayan, Sarinah Thamrin, dan Stasiun Gambir) - Tri Hijrah Saputro; Indung Siti Fatimah; Bambang Sulistyantara (Jurnal Lanskap Indonesia, 2010)
Urban development converts greenery open space become built area, such as office area, settlement, recreation area, shopping  center, etc. The increasing of paving area leads of increasing of air temperature,decreasing thermal comfort, reflecting the phenomena of Urban Heat Islands. It  could be detected at the microscale to mesoscale, as well as parking lots constructed vast at some urban area.This research was conducted to know change of air temperature and humidity at three urban parking lots (Plaza Senayan, SarinahThamrin, and Stasiun Gambir), was held on May 2005. The resuilt showed that dairy air temperature was increasing from morning, and reaching peak at noon or at 2 pm. Parking lot having tree shading showed 0.33 – 0.84 degree Celcius lower than that of incovering by tree shading. This means tree shading promotes the  parking lots with thermal comfort.